Predictors of psychiatric emergency department visits within twelve months post-inpatient psychiatric discharge in Alberta, Canada - Hossam Eldin Elgendy; Reham Shalaby; Ernest Owusu; Wanying Mao; Belinda Agyapong; Wes Vuong; Ejemai Eboreime; Nnamdi Nkire; Yifeng Wei; Vincent I. O. Agyapong (PLoS ONE, 2026)
Background Psychiatric emergency department (ED) visits following discharge from inpatient psychiatric care remain a significant challenge for mental health systems and may reflect gaps in continuity of care and community support. While sociodemographic and clinical predictors of recurrent ED utilization have been widely studied, the role of inpatient satisfaction and transitional care interventions in predicting post-discharge psychiatric ED visits remains less clear. Objectives This study aimed to examine predictors of psychiatric ED visits within 12 months following discharge from acute psychiatric inpatient units, with particular focus on inpatient satisfaction, prior ED utilization, intervention exposure, sociodemographic characteristics, and clinical factors. Methods This observational cohort analysis used data from participants recruited through a pragmatic stepped-wedge transitional care study in Alberta, Canada. A multivariable logistic regression model was conducted to identify predictors of psychiatric ED visits within 12 months post-discharge. Predictor variables included intervention group [treatment as usual (TAU), supportive text messaging (SMS), and supportive text messaging combined with peer support (SMS + PS)], prior ED visits within 6 months before index admission, inpatient satisfaction, sociodemographic variables, and clinical characteristics. Results The study included 1,070 participants. Prior psychiatric ED visits within 6 months preceding the index admission emerged as the strongest predictor of post-discharge psychiatric ED utilization. Unemployment and housing instability were also significantly associated with increased likelihood of ED visits within 12 months following discharge. In contrast, inpatient satisfaction, intervention group, gender, ethnicity, relationship status, resilience, wellbeing, depression, and anxiety measures were not independently associated with post-discharge psychiatric ED visits. Conclusion Psychiatric ED visits following discharge were primarily associated with prior ED utilization and socioeconomic factors, particularly unemployment and housing instability. Although inpatient satisfaction represents an important component of patient-centered psychiatric care, it was not independently associated with subsequent psychiatric ED visits in this cohort. These findings highlight the importance of addressing structural and social determinants alongside transitional care planning to reduce recurrent psychiatric ED utilization.